A Cost Comparison Analysis of Adjuvant Radiation Therapy Techniques after Breast‐Conserving Surgery. Issue 2 (7th January 2013) - Lanni, Thomas; Keisch, Martin; Shah, Chirag; Wobb, Jessica; Kestin, Larry; Vicini, Frank
Abstract The aim of this study is to perform a cost analysis to compare adjuvant radiation therapy schedules following breast conserving surgery. Treatment planning and delivery utilization data were modeled for a series of 10 different breast RT techniques. The whole breast (WB) regimens consisted of: (1) Wedge based WB (25 fractions [fx]), (2) WB using IMRT, (3) WBRT with a boost (B), (4) WBRT using IMRT with a B, (5) Canadian WB (16 fx) with 3D‐CRT, and (6) Canadian using IMRT. The accelerated partial breast irradiation (APBI) regimens included (7): APBI using 3D‐CRT, (8) IMRT, (9) single channel balloon, and (10) multi‐channel balloon. Costs incurred by the payer (i.e., direct medical costs) were taken from the 2011 Medicare Fee Schedule. Among all the different regimens examined, Canadian 3D‐CRT and APBI 3D‐CRT were the least costly whereas WB using IMRT with a B was the most expensive. Both APBI brachytherapy techniques were less costly than conventional WB with a B. In terms of direct medical costs, the technical component accounted for most, if not all, of the disparity among the various treatments. A general trend of decreasing RT costs was observed with further reductions in overall treatment time for WBRT techniques, but not all of the alternative treatment regimens led to similar total cost savings. APBI using brachytherapy techniques was less costly than conventional WBRT with a standard boost.